A Scoping Review of Social Media Use in Social Work Practice. Issue 3 (3rd May 2016) - Chan, Chitat
Abstract : The trend of using social media in social work is increasing, but research which systematically reviews and evaluates their uses in actual practice is limited. This article reviews the social work literature to identify the uses, benefits, and limitations of social media in social work practice, and identifies current gaps in the literature to provide recommendations for future social work research. Articles in 64 social work journals published between 2000 and 2014 were screened and analyzed. The included articles ( n  = 20) were analyzed with particular reference to their level of evidence and ways of social media use. The methodological quality of the studies in this review was low, and this was consistent with the findings of recent systematic reviews of social media use in medical healthcare. The findings initially suggested that social media can potentially contribute to various social work processes, including: service user engagement, need assessment, intervention, and program evaluation. Limitations include lack of quality control, reliability, confidentiality, and privacy. In social work, the dominant research concern in social media is more about professional ethics than their application in intervention. Implications for research and practice are discussed.